ANALISIS LAPORAN KEUANGAN DALAM MENGUKUR KINERJA KEUANGAN PADA PT NET VISI MEDIA TBK - Azizah, Suli Nur; Hartutik, Sri; Kherani, Evi (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to evaluate the financial performance of PT Net Visi Media Tbk using financial ratio analysis, including liquidity, solvency, profitability, and activity ratios. The data analyzed comes from the company’s financial reports for the period of 2020-2023. The analysis results indicate that the company’s liquidity and solvency ratios are below industry standards, suggesting difficulties in meeting short-term obligations and a high dependence on debt. Furthermore, the activity and profitability ratios reveal that the company has not optimally utilized its assets and equity to generate profits. Based on these findings, it is recommended that the company reevaluate its financial and operational strategies to improve future performance